1985
DOI: 10.1007/bf02554050
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal obstruction due to Ascaris lumbricoides mimicking intussusception

Abstract: Two children were admitted for clinical and radiologic signs of small-bowel obstruction. Examination revealed an abdominal mass that was suspected of being a mass of intussusception. Bowel obstruction caused by Ascaris lumbricoides was found at surgery. The laboratory, radiologic, and surgical findings are presented with a short review of the literature with emphasis on diagnosis, incidence, complications, and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1988
1988
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…We then looked at data given in case reports, noting the total worm burden (as counted at surgery, autopsy, or after an anthelmintic), age and outcome (survival/death). Only 24 case reports (Watson 1920;Baugh 1923;Alles 1924;Levin & Porter 1924;Watkins & Moss 1924;Hsu et al 1940;Jenkins & Beach 1954;Aiken & Dickman 1957;Cole 1965;Crane et al 1965;Gandhi 1965;Piggott et al 1970;BustamenteSarabia et al 1979;Rathi et al 1981;Katz et al 1985;Baird et al 1986; Mpairwe 1991) which specified all of the above were found among 53 publications which described a total of more than 1000 patients.…”
mentioning
confidence: 99%
“…We then looked at data given in case reports, noting the total worm burden (as counted at surgery, autopsy, or after an anthelmintic), age and outcome (survival/death). Only 24 case reports (Watson 1920;Baugh 1923;Alles 1924;Levin & Porter 1924;Watkins & Moss 1924;Hsu et al 1940;Jenkins & Beach 1954;Aiken & Dickman 1957;Cole 1965;Crane et al 1965;Gandhi 1965;Piggott et al 1970;BustamenteSarabia et al 1979;Rathi et al 1981;Katz et al 1985;Baird et al 1986; Mpairwe 1991) which specified all of the above were found among 53 publications which described a total of more than 1000 patients.…”
mentioning
confidence: 99%
“…A total of 360 patients were studied: age range, 9 months-14.6 years, mean ± standard deviation (SD), 6 Abdominal pain was the leading symptom (Table 1). Colicky pain with periumbilical distribution was the most type of pain present in 276 patients (77%).…”
Section: Resultsmentioning
confidence: 99%
“…Regardless of the worm burden, the intestinal form of ascariasis must be treated to avert possible complications. If conservative therapy is not successful, diagnosis is not certain, or the obstruction is complete, surgical intervention will be necessary [6, 7]. This study evaluated prospectively the clinical presentation, management, operative modality used, and various peroperative findings of surgical intervention for symptomatic intestinal ascariasis in a children.…”
Section: Introductionmentioning
confidence: 99%
“…Other diseases mimicking intussusception include small bowel abscess, enterolith, Ascaris lumbricoides , cecal fecalith, complicated Rapunzel syndrome, appendicitis in duplex appendix, tuberculosis and eosinophilic gastroenteritis with perforation …”
Section: Discussionmentioning
confidence: 99%